ANALISIS SIKUEN STRATIGRAFI DAN PEMODELAN FASIES FORMASI TANJUNG BERDASARKAN DATA LOG SUMUR DAN DATA INTI BATUAN PADA LAPANGAN MIR CEKUNGAN BARITO, KALIMANTAN SELATAN - Muhammad Ilham Ridwan; Hadi Nugroho; Yoga Aribowo; Mill Sartika Indah; Perdana Rakhmana Putra (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Increased consumption of energy resources of oil and gas, exploration and exploitation process results performed optimally. Interpretation of subsurface using well log data combined with geological disciplines becomes very important in increasing exploration. Location of the study lies in one of the field located in the Barito basin of South Kalimantan province owned by Pertamina UTC. This research was done in the implementation of the final project addressed the subject of mapping subsurface using sequence stratigraphic approachs.The purpose of this research is to determine the type of lithology, facies and depositional environment, sequence stratigraphy, distribution of sedimentation and facies modelling Tanjung Formation in the MIR field. This research is using descriptive method and analytical methods. Descriptive method is a method that does some literature review. While the analysis method is using qualitative analysis to determine the type of lithology, stratigraphy and facies modeling sequence. This analysis uses software petrel 2009 in an analysis of well logs in the distribution of lithology, stratigraphic marker horizon correlation, subsurface mapping and facies modelling.Based on the results of the data analysis and discussion, it can be interpreted that the Tanjung Formation in the MIR field has a type silisiklastik sandstone lithology (sandstone), shale (shale) and coal (coal) with depositional environment in estuarine area. The results of the analysis of stratigraphic marker is 2 MRS (Maximum Surface Regression), 5 FS (Flooding Surface), 2 MFS (Maximum Flooding Surface) and 1 SB (Sequence Boundary) with sequence stratigraphic unit 2 Lowstand System Track (LST), 2 Transgressive System Track (TST) and Highstand System Track 1 (HST). Direction of sedimentation cycles in Tanjung Formation sequence stratigraphy approach leads to Northwest – South east (NNW - SSE). Facies models are divided into two zones: the ZR1 zone and ZR2 zone, where the zone was conducted to calibrate the rock core data. Based on core analysis Estuary facies rocks have Chanel and Tidal flat on Keywell. According to core data support and electrofasies in the study site, there are 3 facies deposition environmental: Chanel Estuary , Tidal flat and Tidal Bars.